Implementasi metode NIOSH dan analisa QEC pada alat potong ranting - Zufri Hasrudy Siregar; Margie Subahagia Ningsih (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
This research is the design of  new technology which is  simple by engineering hydraulic system and  principles of hand grip which functions  as adjustable twig clipper  that is ergonomic, with the normal length of 1.5 meters,  maximum length of 3 meters., weight of 2.8 kg,  the length of grip range  of 94 mm and handlebar diameter of 52 mm. This research used the method of ergonomic analysis to identify the suitability of the device with human by taking 95 percentile. From the findings, the hand grip diameter obtained is 54, 29 mm while the hand palm width is 97.87 mm, and the maximum pressure required to cut the branch is 522.29 kg/cm2 with a diameter of 1 cm that is for the type of clove twig. In addition, from the NIOSH analysis, it is obtained that the required weight is 4.89 Kg while from the QEC method, the highest score percentage is 47.62. This means that it is necessary to improve the equipment in the future. In order to prevent tiredness, the suggested working duration is 8.40 minutes and 7.14 minutes for resting time. From the results of research, it can be concluded that this device still needs to be improved in the future. In addition, the usage time is quite short and it is only functioned for harvesting clove and harvesting other similar with maximum diameter of 1 cm.